A Civil Society Deferred : The Tertiary Grip of Violence in the Sudan - Gallab, Abdullahi A. (Book collections on Project MUSE., 2011)
"A Civil Society Deferred chronicles the socio-political history and development of violence in the Sudan and explores how it has crippled the state, retarded the development of a national identity, and ravaged the social and material life of its citizens. It offers the first detailed case studies of the development of both a colonial and postcolonial Sudanese state and grounds the violence that grips the country within the conflict between imperial rule and a resisting civil society."--Publisher's site.